2020
DOI: 10.3390/nu12061837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Flaxseed Lignan Intervention on Circulating Bile Acids in a Placebo-Controlled Randomized, Crossover Trial

Abstract: Plant lignans and their microbial metabolites, e.g., enterolactone (ENL), may affect bile acid (BA) metabolism through interaction with hepatic receptors. We evaluated the effects of a flaxseed lignan extract (50 mg/day secoisolariciresinol diglucoside) compared to a placebo for 60 days each on plasma BA concentrations in 46 healthy men and women (20–45 years) using samples from a completed randomized, crossover intervention. Twenty BA species were measured in fasting plasma using LC-MS. ENL was measured in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…Given that ENL production is also affected by microbial conversion efficiency of different lignans to enterolignans [ 42 , 43 , 44 , 45 ], the gut microbiota may contribute to inter-individual and population-specific variation in enterolignan exposures. Gut microbial diversity may be responsive to the variety of dietary components resulting from cultural and ethnic differences in dietary patterns [ 33 ], although in our study, alpha diversity did not differ in the AA or EA at baseline or in response to FS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ENL production is also affected by microbial conversion efficiency of different lignans to enterolignans [ 42 , 43 , 44 , 45 ], the gut microbiota may contribute to inter-individual and population-specific variation in enterolignan exposures. Gut microbial diversity may be responsive to the variety of dietary components resulting from cultural and ethnic differences in dietary patterns [ 33 ], although in our study, alpha diversity did not differ in the AA or EA at baseline or in response to FS.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that observed differences in ENL production and microbiome composition between AA and EA could be relevant to population-specific differences in chronic disease prevalence. For example, cross-sectional studies have reported an inverse relationship between ENL excretion and circulating secondary bile acids [ 63 , 64 ], bacterial metabolites associated with increased risk of CVD, cirrhosis [ 65 ], and CRC [ 45 , 64 ]. In our study, Lachnoclostridium was inversely associated with ENL production in EA.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids, which were essential metabolic regulators, have gained more and more attention for their potential functions in lipid disorder therapeutics as specific targets. Bile acids, converted from hepatic cholesterol, are secreted into the intestinal tract in response to extrinsic stimulation, in which primary bile acids will develop into secondary bile acids by microbial biotransformation . Bile acids consist of various molecular species, which were reported in association with a variety of chronic diseases, such as nonalcoholic fatty liver disease .…”
Section: Introductionmentioning
confidence: 99%
“…In our study population, there were no baseline differences in demographic and lifestyle factors between individuals classified as low-and high-ENL excreters [6,24]. Generally, in cross-sectional, observational studies, factors that affect ENL measures include intake of lignan-rich foods, antibiotic use, body mass index, smoking, sex and age [7].…”
Section: Discussionmentioning
confidence: 76%